2020
DOI: 10.1080/20002297.2020.1808425
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of 2-methacryloyloxyethyl phosphorylcholine polymer on the adherence of bacteria causing upper respiratory tract infection

Abstract: Objective: We aimed to investigate the inhibitory effect of 2-methacryloyloxyethyl phosphorylcholine (MPC) polymer on the adherence of Streptococcus pneumoniae (Spn) and nontypeable Haemophilus influenzae (NTHi) in vitro and in vivo. Materials and Methods: Phosphorylcholine (PC) expression of 21 strains each of Spn and NTHi was evaluated using fluorescence-activated cell sorting; the adherence of bacteria to Detroit 562 cells and to the nasal mucosa of BALB/c mice was determined. MPC polymermediated inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…High PC expression is considered to increase S. pneumoniae and H. in uenzae virulence [17]. For instance, it has been reported that S. pneumoniae with high PC expression causes more invasive infection than that with low PC expression [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High PC expression is considered to increase S. pneumoniae and H. in uenzae virulence [17]. For instance, it has been reported that S. pneumoniae with high PC expression causes more invasive infection than that with low PC expression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Detroit 562 cells (CCL-138; ATCC, Manassas, VA, USA), a human pharyngeal carcinoma epithelial cell line, were grown to con uence in minimal essential medium (Nacalai Tesque Inc., Kyoto, Japan) supplemented with 1 mM sodium pyruvate (Nacalai Tesque), 10% fetal bovine serum (Invitrogen, San Diego, CA, USA), penicillin (100 U/mL), and streptomycin (100 µg/mL; Nacalai Tesque) at 37°C in a 5% CO 2 incubator, as previously described (Iuchi et al, 2020). The cells were harvested using trypsin ( nal concentration, 0.02%) and ethylenediaminetetraacetic acid ( nal concentration, 0.02%; Nacalai Tesque) and seeded at a density of 2 × 10 4 viable cells per well in a 96-well BD Falcon tissue culture plate with a low-evaporation lid (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Detroit 562 cells (CCL-138; ATCC, Manassas, VA, USA), a human pharyngeal carcinoma epithelial cell line, were grown to confluence in minimal essential medium (Nacalai Tesque Inc., Kyoto, Japan) supplemented with 1 mM sodium pyruvate (Nacalai Tesque), 10% fetal bovine serum (Invitrogen, San Diego, CA, USA), penicillin (100 U/mL), and streptomycin (100 μg/mL; Nacalai Tesque) at 37 °C in a 5% CO 2 incubator as previously described [ 29 ]. The cells were harvested using trypsin (final concentration, 0.02%) and ethylenediaminetetraacetic acid (EDTA; final concentration, 0.02%; Nacalai Tesque) and seeded at a density of 2 × 10 4 viable cells per well in a 96-well BD Falcon tissue culture plate with a low-evaporation lid (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Detroit 562 cells (CCL-138; ATCC, Manassas, VA, USA), a human pharyngeal carcinoma epithelial cell line, were grown to con uence in minimal essential medium (Nacalai Tesque Inc., Kyoto, Japan) supplemented with 1 mM sodium pyruvate (Nacalai Tesque), 10% fetal bovine serum (Invitrogen, San Diego, CA, USA), penicillin (100 U/mL), and streptomycin (100 μg/mL; Nacalai Tesque) at 37ºC in a 5% CO 2 incubator as previous described [16]. The cells were harvested using trypsin ( nal concentration, 0.02%) and ethylenediaminetetraacetic acid (EDTA; nal concentration, 0.02%; Nacalai Tesque) and seeded at a density of 2 × 10 4 viable cells per well in a 96-well BD Falcon tissue culture plate with a lowevaporation lid (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Cell Culturementioning
confidence: 99%